Low-cost potentiometric sensor based on a molecularly imprinted polymer for the rapid determination of matrine in herbal medicines. Issue 6 (2nd November 2019) - He, Yeshan; Yang, Tan; Mo, Hailan; Chen, Tiane; Feng, Jianfang; Zhang, Wei
Abstract: A low-cost potentiometric sensor based on a molecularly imprinted polymer was developed for the determination of matrine in herbal medicine samples. The imprinted material was synthesized by the use of matrine as template, methacrylic acid (MAA) as the monomer, ethylene glycol dimethyl acrylate (EGDMA) as the cross linker, 2, 2′-azo-bisisobutyronitrile (AIBN) as the initiator, and toluene and dodecanol as the porogenic agent. The electrode sensing membrane was fabricated by incorporating the ground imprinted particles into the polyvinyl chloride substrate that was subsequently incorporated into a laboratory constructed ion-selective electrode. The prepared imprinted sensor exhibited a rapid Nernst response across the concentration range from 1 × 10 −5 to 1 × 10 −1 M with a detection limit equal to 9.3 × 10 −6 M. The analytical capabilities support the direct determination of matrine in herbal medicine. The analytical results were verified by a standard ultraviolet absorption spectrophotometry protocol. The proposed sensor manifested a series of advantages, including high selectivity and sensitivity, enhanced stability and low cost, that provides a wide number of potential applications for herbal analysis.